Assessment of the functional state of skin microhemodynamics by the methods of Doppler fluumetry and speckle-metry - N. D. Abramovich; S. K. Dick; L. A. Vasilevskaya; I. I. Khludeyev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The characteristics of blood microcirculation in human tissues have been investigated by recording and analyzing a dynamic speckle pattern. Methodical approaches have been proposed for evaluating the obtained data in order to verify speckle measurements using the widely used Doppler flowmetry technique.